Peranan Orangtua Dalam Memberikan Bimbingan PAK Menurut Amsal 22:6 Terhadap Perilaku Anak Umur 3-5 Tahun - Siregar, Solamit; Kristiani, Kristiani; Cinta, Yesa (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
Family is the smallest social unit that has an important role in shaping children's character. Parents, as the main figures in the family, have a great responsibility in educating and guiding children, especially in terms of Christian religious education. This study aims to describe the responsibility of parents in providing Christian Religious Education guidance according to Proverbs 22:6 on the behavior of children aged 3-5 years. This study uses a descriptive qualitative method by analyzing the text of Proverbs 22:6 and various related scientific sources. The results of the study indicate that the right parenting pattern from parents has a major influence on children's spiritual growth. Parents play an important role in instilling spiritual values from an early age, providing good examples, and creating a conducive environment for children's development. Proper education from a young age will shape children's characters that do not deviate from God's path until adulthood. This study provides an in-depth understanding of the meaning of Proverbs 22:6 and its relevance in early childhood education, with a focus on the role of parents as the main guides in shaping children's character according to Christian teachings. This study also highlights the importance of the role of parents as authoritative figures who have a divine mandate in educating children, which distinguishes it from other studies that may only focus on the psychological or social aspects of child rearing.